The Comparison between Native Speakers of Indonesian and BIPA Learners in Producing Email Requests - ANDIKA EKO PRASETIYO (Indonesian Research Journal in Education |IRJE|, 2019)
This study examined a comparison between Native Speakers (NS) of Indonesian and Indonesian language as a foreign language (Bahasa Indonesia untuk Penutur Asing - BIPA) learners in making email requests. In particular, this study analysed the different aspects of pragmatics of variations in structure and politeness in emails. This study involved nine NS of Indonesian who were studying master’s level programs at the University of Melbourne, and eighteen BIPA learners who took the subject Indonesian 4 in Semester 2, 2018 at the University of Melbourne. Participants wrote an email request based on a given scenario, which was requesting leave in the context of a workplace in Indonesia. The data were obtained by providing participants a description of the scenario, which prompted them to write an email request asking permission to take time off work. However, participants had freedom in terms of the style and structure of the email. In general, this study aimed to examine how their pragmatics varies, especially in terms of structure and politeness.